إدارة المخاطر المالیة للاستصناع وضمانات تطبیقه في المصارف الاسلامیة عبر بناء محفظة استثماریة مثلي ’’حالة مصرف البرك - بن بایر الحبیب; حاكمي نجیب الله (Finance and Business Economies Review, 2017)
: The study examines the extent to which Islamic banks rely on Istisna'a to build their investment portfolio based on return and risk. The use of optimization functions in the financial statements of Al Baraka Bank for the years 2006 to 2012 shows that the Bank tends to allocate high rates of margin formulas, Although Istisna'a has a high rate of return, but its high risk has led Al Baraka Bank to reduce its financial allocation.